Effect of Genetic Variability in the CYP4F2, CYP4F11, and CYP4F12 Genes on Liver mRNA Levels and Warfarin Response - Zhang, J. E.; Klein, Kathrin; Jorgensen, Andrea L.; Francis, Ben; Alfirevic, Ana; Bourgeois, Stephane; Deloukas, Panagiotis; Zanger, Ulrich M.; Pirmohamed, Munir (Frontiers in Pharmacology, 2017)
Genetic polymorphisms in the gene encoding cytochrome P450 (CYP) 4F2, a vitamin K oxidase, affect stable warfarin dose requirements and time to therapeutic INR. CYP4F2 is part of the CYP4F gene cluster, which is highly polymorphic and exhibits a high degree of linkage disequilibrium, making it difficult to define causal variants. Our objective was to examine the effect of genetic variability in the CYP4F gene cluster on expression of the individual CYP4F genes and warfarin response. mRNA levels of the CYP4F gene cluster were quantified in human liver samples (n=149) obtained from a well characterized liver bank and fine mapping of the CYP4F gene cluster encompassing CYP4F2, CYP4F11 and CYP4F12 was performed. Genome-wide association study (GWAS) data from a prospective cohort of warfarin-treated patients (n=711) was also analysed for genetic variations across the CYP4F gene cluster. In addition, SNP-gene expression in human liver tissues and interactions between CYP4F genes were explored in silico using publicly available data repositories. We found that SNPs in CYP4F2, CYP4F11 and CYP4F12 were associated with mRNA expression in the CYP4F gene cluster. In particular, CYP4F2 rs2108622 was associated with increased CYP4F2 expression while CYP4F11 rs1060467 was associated with decreased CYP4F2 expression. Interestingly, these CYP4F2 and CYP4F11 SNPs showed similar effects with warfarin stable dose where CYP4F11 rs1060467 was associated with a reduction in daily warfarin dose requirement (~1 mg/day, Pc = 0.017), an effect opposite to that previously reported with CYP4F2 (rs2108622). However, inclusion of either or both of these SNPs in a pharmacogenetic algorithm consisting of age, body mass index (BMI), gender, baseline clotting factor II level, CYP2C9*2 rs1799853, CYP2C9*3 rs1057910 and VKORC1 rs9923231 improved warfarin dose variability only by 0.5-0.7% with an improvement in dose prediction accuracy of ~1-2%. Although there is complex regulation across the CYP4F gene cluster, the opposing effects between the 2 SNPs in the CYP4F gene cluster appear to compensate for each other and their effect on warfarin dose requirement is unlikely to be clinically significant.